2013
DOI: 10.1590/s1984-29612013005000004
|View full text |Cite
|
Sign up to set email alerts
|

Ticks on birds in a savanna (Cerrado) reserve on the outskirts of Uberlândia, Minas Gerais, Brazil

Abstract: We report tick infestations on birds, in the environment and on domestic animals in a non-forested phytophysiognomy, the savanna-like Cerrado sensu stricto, in a natural reserve on the outskirts of the urban area of Uberlândia, Minas Gerais, Brazil. Overall, 238 birds within 50 species, 15 families and six orders were caught. Passeriformes were the most numerous, with 216 birds (90.75%), among which 22 had ticks (n = 31). Within this order, the prevalence of tick infestation was 10.2%, and the abundance and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…The adults of this species are commonly found in the anteaters (Xenarthra, Pilosa) (ARAGÃO, 1936;JONES et al, 1972;BECHARA et al, 2002;LABRUNA et al, 2002a;DANTAS-TORRES et al, 2010;MARTINS et al, 2014a). Subadults, especially nymphs, seem to feed primarily on birds (JONES et al, 1972;LABRUNA et al, 2007a;OGRZEWALSKA et al, 2009aOGRZEWALSKA et al, , 2011aOGRZEWALSKA et al, , 2012aTOLESANO-PASCOLI et al, 2010;LUZ et al, 2012;MARTINS et al, 2013;PASCOAL et al, 2013;TORGA et al, 2013;LUGARINI et al, 2015;NOVAKOVA et al, 2015;RAMOS et al, 2015;WITTER et al, 2016 SABATINI et al, 2010;SZABÓ et al, 2013a, b).…”
Section: Amblyomma Brasiliense Aragão 1908 Occurs Inmentioning
confidence: 99%
“…The adults of this species are commonly found in the anteaters (Xenarthra, Pilosa) (ARAGÃO, 1936;JONES et al, 1972;BECHARA et al, 2002;LABRUNA et al, 2002a;DANTAS-TORRES et al, 2010;MARTINS et al, 2014a). Subadults, especially nymphs, seem to feed primarily on birds (JONES et al, 1972;LABRUNA et al, 2007a;OGRZEWALSKA et al, 2009aOGRZEWALSKA et al, , 2011aOGRZEWALSKA et al, , 2012aTOLESANO-PASCOLI et al, 2010;LUZ et al, 2012;MARTINS et al, 2013;PASCOAL et al, 2013;TORGA et al, 2013;LUGARINI et al, 2015;NOVAKOVA et al, 2015;RAMOS et al, 2015;WITTER et al, 2016 SABATINI et al, 2010;SZABÓ et al, 2013a, b).…”
Section: Amblyomma Brasiliense Aragão 1908 Occurs Inmentioning
confidence: 99%
“…For the most part, however, studies have reported the occurrence of immature stages (larvae and nymphs) of Amblyomma spp. on wild birds that were captured in different areas of the Brazilian Cerrado and Atlantic Forest biomes (Marini et al 1996, Neves et al 2000, Storni et al 2005, Labruna et al 2007, Ogrzewalska et al 2008, 2011b, Tolesano-Pascoli et al 2010, Santolin et al 2012, Pacheco et al 2012, Amaral et al 2013, Pascoal et al 2013, Sanches et al 2013, Torga et al 2013. Within the Amazon biome, only a single Brazilian study, in the State of Pará, has systematically evaluated wild birds for ticks .…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, dragging was the method most used for tick collection, followed by CO 2 traps (SZABÓ et al, 2007;CANÇADO et al, 2008;OGRZEWALSKA et al, 2009;TOLESANO-PASCOLI et al, 2010;VERONEZ et al, 2010;GARCIA et al, 2013;PASCOAL et al, 2013) and, more recently, visual searching in forest environments (LABRUNA et al, 2005;SILVA et al, 2008;SZABÓ et al, 2009). Few evaluations of tick sampling methods in Brazil have been made (TERASSINI et al, 2010;GUEDES et al, 2012).…”
Section: Introductionmentioning
confidence: 99%